Curiosity Unveiled: A Holistic Systematic Literature Review of Boarding School Students - Ghazali, Mas Yanti; Ahmad, Anuar; Mansor , Azlin Norhaini (PT. Riset Press International, 2025)
This systematic literature review explores the diverse aspects of full-boarding school students worldwide. Despite its significance, there is a lack of a comprehensive synthesis of existing research on students in boarding schools. This review aims to bridge this gap by analyzing and structuring the available literature. The study employed the PRISMA approach and conducted systematic searches in academic databases such as Scopus and Web of Science to gather comprehensive studies, reviews, and articles related to students in boarding schools. The analysis was categorized into four themes that unveiled the objective of this study by utilizing advanced search techniques and keywords such as (1)